A comparative study of healthy lifestyle behaviors and related factors among Iranian male and female adolescents: a cross-sectional study. - Shirzadi, Shayesteh.; Borzu, Zahra Arab.; Jahanfar, Shayesteh.; Alvani, Somayeh.; Balouchi, Maliheh.; Gerow, Hadiseh Jalali.; Zarvekanloo, Soudabeh.; Seraj, Fatemeh. (Tufts University. Tisch Library., 2025)
Keywords: Health Behavior, Healthy lifestyle, Adolescent, Male, Female, Iran.; Springer Open.